Boundaries of life and death from the viewpoint of Shi'i Islamic jurisprudence and the consequences in the field of Islamic bioethics - Sobotková, Veronika (Religio, 2019)
The article provides an overview of the various opinions, theories and debate concerning the boundaries of human life (the beginning and end of human life) in Shi'i Islam and the important consequences in terms of the use of different medical technologies. It considers this issue from the perspective of Shi'i jurisprudence in contemporary Iran, in particular on the basis of the published legal decisions of important high-ranking clerics and based on the knowledge shared within the Islamic seminaries in Qom. The study first describes various theories concerning the exact beginning of human life and the phases of Qur'anic embryogenesis. The issue of therapeutic abortions is then described and the different views of important Iranian clerics are presented on whether therapeutic abortions can be allowed or not and under what conditions and based on which fiqh arguments. The study further addresses the definition of human death, specifically the very extraordinary case of people with acute brain damage (coma, vegetative state and brain death). It discusses whether brain activity or heart activity is essential for determining human death and presents the views of the clerics on this issue and consequently whether disconnection from medical devices (euthanasia) and organ donation are allowed in these cases. This article draws conclusions on the status of the human foetus (especially before ensoulment) and addresses the reflection over the sources of Shi'i Islamic bioethics, in which Islamic jurisprudence has obviously prevailed over Islamic ethics. Together with the modern methodology of Shi'i jurisprudence and using rationality ('aql) as a basic source, this becomes the basis of a pragmatic and rational attitude towards medical biotechnologies.